Peran Hukum Dalam Meningkatkan Etika Bisnis Di Perusahaan Media Online - Ni Putu Ega Maha Wiryanthi (Kertha Wicaksana, 2025)
The problem in this research is that many online media companies violate business ethics, thus having a wide impact. The aim of this research is to explore the role of law in supporting the application of business ethics in online media companies. The approach used is a qualitative approach with a literature study method, which focuses on collecting information from various relevant reference sources, such as books, journals, articles and other written sources. The information obtained will be analyzed systematically and compiled into a research report. It is hoped that this research can increase awareness regarding the importance of collaboration between law and ethics in creating ethical and responsible business practices, especially in the context of online media companies in Indonesia.